Penyelenggaraan Event Premium Music Experience sebagai Kunci Kepuasan Nasabah Bank OCBC - Chang, Keith Prasethio; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study examines marketing communication through events that aim to associate products with popular activities such as sports, concerts, bazaars, or festivals. Premium Music Experience (PME) is an exclusive music concert event held by OCBC for its customers as part of its marketing communication strategy. This study aims to measure the influence of PME event marketing communication and event quality on OCBC Bank customer satisfaction. The study uses the theory of marketing communication, event marketing, event quality, and customer satisfaction. A quantitative approach with a correlational method was applied through a questionnaire survey to 100 OCBC customers who had participated in PME. The results of the study indicate that PME event marketing communication has a positive and significant influence on customer satisfaction. In addition, event quality also has a positive and significant influence. These findings confirm that organizing quality events, with effective communication, can meet customer expectations, increase satisfaction, create memorable experiences, and encourage customer loyalty. Such events allow companies to build emotional relationships with customers, improve brand image, and encourage recommendations from customers to other parties. This study provides practical insights for companies in designing event-based marketing communication strategies. Penelitian ini mengkaji komunikasi pemasaran melalui event yang bertujuan mengasosiasikan produk dengan aktivitas populer seperti olahraga, konser, bazar, atau festival. Premium Music Experience (PME) adalah acara konser musik eksklusif yang diadakan OCBC bagi nasabah sebagai bagian dari strategi komunikasi pemasaran. Penelitian ini bertujuan mengukur pengaruh event marketing komunikasi PME dan kualitas acara (event quality) terhadap kepuasan nasabah Bank OCBC. Penelitian menggunakan teori komunikasi pemasaran, event marketing, event quality, dan kepuasan pelanggan. Pendekatan kuantitatif dengan metode korelasional diterapkan melalui survei kuesioner kepada 100 nasabah OCBC yang pernah mengikuti PME. Hasil penelitian menunjukkan bahwa event marketing komunikasi PME memiliki pengaruh positif dan signifikan terhadap kepuasan nasabah. Selain itu, event quality juga berpengaruh positif dan signifikan. Temuan ini menegaskan bahwa penyelenggaraan acara yang berkualitas, dengan komunikasi yang efektif, dapat memenuhi harapan pelanggan, meningkatkan kepuasan, menciptakan pengalaman berkesan, serta mendorong loyalitas pelanggan. Acara semacam ini memungkinkan perusahaan untuk membangun hubungan emosional dengan nasabah, meningkatkan citra merek, serta mendorong rekomendasi dari pelanggan kepada pihak lain. Penelitian ini memberikan wawasan praktis bagi perusahaan dalam merancang strategi komunikasi pemasaran berbasis event.